Developing a spoken corpus for South Saami language teaching and learning - Vinka, Mikael; Waldmann, Christian; Kroik, David; Sullivan, Kirk P. H. (Umeå University, 2015)
In Chapter 5 Mikael Vinka, Christian Waldmann, David Kroik and Kirk Sullivan consider the creation of corpora in the Saami language and how these can be used to support minority language education in pre-school. Using examples both from the CHILDES database and from South Saami they illustrate how corpora may support the development of culturally relevant teaching materials.